Analysis Of The Influence Of Brand Equity Dimensions On Consumer Buying Interest In Fashion Products In Bogor City: Case Study Of Consumers Erigo - Mumuh Mulyana; Brillian Jodi Firmansyah; Febry Lodwyk Rihe Riwoe; Mashadi Mashadi (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to determine how the influence of brand equity dimensions on consumer purchasing interest in Erigo products in Bogor City. The brand equity dimensions consist of brand awareness, perceived quality, brand association, and brand loyalty. This study uses a descriptive quantitative approach with a data collection method in the form of a questionnaire to 196 respondents. The sampling technique in this study was carried out using a non-probability technique in the form of purposive sampling. This technique is carried out by determining the sample criteria in the form of Erigo consumers in Bogor City. The data analysis technique in this study uses SEM (Structural Equation Modeling) analysis. This study found that the dimensions of equity, brand awareness and brand association do not have a significant effect on consumer purchasing interest in Erigo products in Bogor City. The dimensions of perceived quality and brand loyalty have a significant effect on consumer purchasing interest in Erigo products in Bogor City. Keywords : Brand Equity, Buying Interest, Erigo , Influence